Productivity Analysis of Fuyu Oil Shale In-Situ Pyrolysis by Injecting Hot Nitrogen - Zhao, Shuai; Li, Qiang; Lu, Xiaoshu; Sun, Youhong (MDPI, 2021)
In this paper, the effect of heat injection on productivity of Fuyu oil shale during in-situ pyrolysis was studied by using heat flow coupling analysis method. It is found that fluid conducts heat transmission to the oil shale stratum mainly along the fissure formed by hydraulic fracturing. With the increase of heating time, the oil shale on both sides of fissures were effectively pyrolyzed, and the porosity of the formation increases and the diffusion range of the nitrogen to the oil shale stratum is also improved. After 200 days, the oil shale around the fractures first reaches the pyrolysis temperature, and 700 days later, the average temperature of the oil shale stratum reaches 500 °C; therefore, the whole oil shale can be effectively pyrolyzed. Productivity analysis shows that the best exploitation temperature is 500 °C. When the gas injection rate is in the range of 1.0~11.0 m3/min, different degrees of heat loss will occur, and the output is also different. The pyrolysis time reaches 100~150 days, showing the peak value of daily production, which is between 0.5~3.2 m3/day. The pressure of displacement fluid affects oil shale product recovery in in-situ pyrolysis. High pressure helps to improve the displacement efficiency of oil and gas products and increase the productivity of oil shale in-situ pyrolysis. The best acting pressure is 9.5 MPa.
Keywords: productivity analysis; numerical simulation; thermal fluid pressure coupling; in-situ pyrolysis; oil shale; fi=Energiatekniikka|en=Energy Technology|